Implications of Environmental Politics in Collaborative Governance and Community Empowerment through Corporate Social Responsibility: A Case Study in Juwiring Village - Dikka Prasetyo; Rina Martini; Fathya Naila Farranajla (Journal of Law, Politic and Humanities, 2025)
This research aims to analyze the implications of environmental politics through a collaborative governance approach in the implementation of PT Tirta Investama's Corporate Social Responsibility (CSR) program in Juwiring Village, Klaten Regency. This qualitative research uses a case study approach, with data collection methods through in-depth interviews, participatory observation, and documentation. The selection of informants used a purposive sampling technique, while data analysis adopted an interactive analysis model. Despite facing challenges related to transparency and coordination, collaborative governance has had a transformative impact on environmental politics in Juwiring Village, especially in terms of strengthening local institutions and integrating CSR programs with regional development. This case study shows a significant transformation in the power relations of natural resource management, from a top-down approach to a more participatory and democratic one, manifested in the formation of the Irrigation Volunteer Forum (FRI) involving various stakeholders. Klaten BAPPEDALITBANG plays an important role as a facilitator, ensuring effective collaboration between the government, private sector and the community. Community empowerment programs through Kelompok Wanita Tani (KWT) and Kelompok Tani (POKTAN) successfully increased the community's capacity in sustainable agriculture. The research concludes that a collaborative approach has the potential to create comprehensive and sustainable solutions to environmental and social challenges. There is potential to deepen the analysis of more specific challenges in the implementation of CSR programs as well as how various stakeholders handle conflicts that may arise in the collaborative process.